Genome-wide methylation profiling in granulosa lutein cells of women with polycystic ovary syndrome (PCOS). (15th January 2020) - Makrinou, E.; Drong, A.W.; Christopoulos, G.; Lerner, A.; Chapa-Chorda, I.; Karaderi, T.; Lavery, S.; Hardy, K.; Lindgren, C.M.; Franks, S.
Abstract: Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder amongst women of reproductive age, whose aetiology remains unclear. To improve our understanding of the molecular mechanisms underlying the disease, we conducted a genome-wide DNA methylation profiling in granulosa lutein cells collected from 16 women suffering from PCOS, in comparison to 16 healthy controls. Samples were collected by follicular aspiration during routine egg collection for IVF treatment. Study groups were matched for age and BMI, did not suffer from other disease and were not taking confounding medication. Comparing women with polycystic versus normal ovarian morphology, after correcting for multiple comparisons, we identified 106 differentially methylated CpG sites with p-values <5.8 × 10 −8 that were associated with 88 genes, several of which are known to relate either to PCOS or to ovarian function. Replication and validation of the experiment was done using pyrosequencing to analyse six of the identified differentially methylated sites. Pathway analysis indicated potential disruption in canonical pathways and gene networks that are, amongst other, associated with cancer, cardiogenesis, Hedgehog signalling and immune response. In conclusion, these novel findings indicate that women with PCOS display epigenetic changes in ovarian granulosa cells that may be associated with the heterogeneity of the disorder.